Exploring relationships between joint hypermobility and neurodevelopment in children (4–13 years) with hereditary connective tissue disorders and developmental coordination disorder. Issue 6 (2nd August 2018) - Piedimonte, Caterina; Penge, Roberta; Morlino, Silvia; Sperduti, Isabella; Terzani, Andrea; Giannini, Maria Teresa; Colombi, Marina; Grammatico, Paola; Cardona, Francesco; Castori, Marco
Abstract : Joint hypermobility (JH) is a common, though largely ignored physical trait with increasing clinical reverberations. A few papers suggest a link between JH and selected neurodevelopmental disorders, such as developmental coordination disorder (DCD). JH is also the hallmark of various hereditary connective tissue disorders (HCTDs). Children with HCTDs may present abnormal neurodevelopment but its manifestations remain undetermined. This study examined 23 children (group 1), aged 4–13 years, with different HCTDs (i.e., 19 with hypermobile Ehlers‐Danlos syndrome (EDS)/hypermobility spectrum disorder, 3 with molecularly confirmed classical EDS, and 1 with Loeys‐Dietz syndrome type 1 due to TGFBR2 mutation) and 23, age‐ and sex‐matched children with DCD (group 2). All underwent 14 different psychometric tests exploring motor, cognitive, executive‐attentive, and emotional‐behavior features. In group 1, 30%, 22%, and 13% patients presented DCD (with or without dysgraphia), learning disabilities, and attention deficit‐hyperactivity disorder, respectively. None had cognitive delay. In group 2, 17% patients presented generalized JH and none had HCTDs. DCD children presented more motor and coordination troubles than HCTDs patients, while quality of life of children with HCTDs resulted more deteriorated due to somatic manifestations and behavioral traits. This study presents the full overview of neurodevelopmental attributes in HCTDs, and compares with standardized tools the neurodevelopmental profile of children with DCD and HCTDs. While the high rate of neurodevelopmental comorbidities in HCTDs deserves attention, the impact of a dysfunctional connective tissue in children with a primary diagnosis of DCD needs more research.